2021
DOI: 10.1111/jcmm.17120
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of SOX B1 genes in glioblastoma multiforme patients

Abstract: Glioblastoma multiforme (GBM) is the most common, malignant and high-grade brain tumour. 1,2 The WHO classification system divides glioma into 4 subtypes and GBM as grade 4 glial tumour has the worst prognosis. 3 The intra-and intertumoral genetic and epigenetic heterogeneity observed in GBM highlights the complexity of cancer. 4 The median survival of GBM patients is around 12-15 months, even with

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 58 publications
(49 reference statements)
0
3
0
Order By: Relevance
“…The results demonstrated that cells increased SOX3 expression lead to enhanced migration and invasion capabilities in vitro [34]. Building on this, Pan et al [52] discovered that reducing SOX3 expression elevates the migration of the U251 glioblastoma cells, as supported by a wound-healing assay, while not influencing the cellular invasive capabilities at 48 hours [52]. Furthermore, research by Shujing et al [38], which targeted SOX3 with its repressor miR-483, found that downregulating SOX3 suppresses both cell migration and invasion, providing insights into the complex role of SOX3 in GBM behavior.…”
Section: Sox3 and Cell Invasion And Migrationmentioning
confidence: 78%
See 1 more Smart Citation
“…The results demonstrated that cells increased SOX3 expression lead to enhanced migration and invasion capabilities in vitro [34]. Building on this, Pan et al [52] discovered that reducing SOX3 expression elevates the migration of the U251 glioblastoma cells, as supported by a wound-healing assay, while not influencing the cellular invasive capabilities at 48 hours [52]. Furthermore, research by Shujing et al [38], which targeted SOX3 with its repressor miR-483, found that downregulating SOX3 suppresses both cell migration and invasion, providing insights into the complex role of SOX3 in GBM behavior.…”
Section: Sox3 and Cell Invasion And Migrationmentioning
confidence: 78%
“…In a comprehensive exploration of SOX3 in glioblastoma, Pan et al [52] through ONCOMINE and CCLE bioinformatic databases found SOX3 overexpression in glioblastoma tissues compared to normal tissues [52]. This was complemented by a prognostic analysis using LinkedOmics and GEPIA databases, which presented a positive correlation between higher SOX3 levels and improved overall survival rates in GBM patients, suggesting SOX3 potential as a prognostic biomarker [52].…”
Section: Sox3 In Glioma and Glioblastoma (Gbm)mentioning
confidence: 99%
“…Among identified target genes, there were members of the SOX genes family, but also tumor suppressor genes, interleukins, and their receptors, previously described to play roles in GBM pathology. In vitro experiments showed that SOX2 downregulation significantly decreases the migratory and invasive properties of GBM cells, indicating that SOX2 may serve as a potential therapeutic target in GBM [ 38 ]. Furthermore, it has been reported that SOX2 could contribute to the self-renewal and proliferation of glioma-initiating cells, which are important for the initiation, propagation, and recurrence of glioma [ 39 ].…”
Section: The Role Of Sox Genes In Glioblastomamentioning
confidence: 99%
“…Furthermore, it has been reported that SOX2 could contribute to the self-renewal and proliferation of glioma-initiating cells, which are important for the initiation, propagation, and recurrence of glioma [ 39 ]. Pan et al performed wide bioinformatics analysis using ONCOMINE, GEPIA (Gene Expression Profiling Interactive Analysis), LinkedOmics, and CCLE (Cancer Cell Line Encyclopaedia) databases to assess the expression profiles and prognostic values of SOXB1 members in GBM [ 38 ]. Their analysis revealed that all three SOXB1 members were upregulated in GBM to varying degrees, compared to the normal tissues, identifying only SOX3 as a potential prognostic biomarker whose increased expression correlated with better overall survival [ 38 ].…”
Section: The Role Of Sox Genes In Glioblastomamentioning
confidence: 99%
See 1 more Smart Citation